Ceramic Powder Bed Laser Sintering (CPBLS) on copper-doped hydroxyapatite: Creation of thin (5–50 μm thick) consolidated ceramic patterns. Issue 13 (1st July 2021) - Bazin, Tiphaine; Rouzé-l'Alzit, François; Demourgues, Alain; Julien, I.; Bertrand, C.; Catros, S.; Cardinal, Thierry; Champion, Eric; Gaudon, Manuel
Abstract: Implants made of ceramics, and more particularly of calcium phosphates (hydroxyapatite: HA, mainly), promoting intimate contact with natural bone are nowadays merging. Addition of copper ions in bio-ceramics is expected to increase the biological compatibilities of bone graft substitutes. Previous works have shown that copper-doped hydroxyapatite (Cu-doped HA) ceramics can be prepared by solid-state sintering between HA and CuO powder mixtures at about 1100 °C; but, copper-substituted HA was found to be metastable leading to apatitic grains and Cu-rich grain boundaries during the sintering process. Ultra-rapid sintering is so needed. Selective laser sintering (SLS) is an additive manufacturing process that possesses the advantage to be based on ultra-fast sintering process under laser irradiation. SLS being used in literature for the application of laser on polymer-ceramic or poymer-metal composites the proper term all along the paper is Ceramic Powder Bed Laser Sintering (CPBLS). To achieve densification of Cu-doped HA ceramics from CPBLS process, one should control the composition/morphology/structure of the powder bed as well as three other important CPBLS parameters: (i) the applied energy from the laser beam, (ii) the laser power and the laser scanning speed, (iii) the distance between two successive lased lines. In this paper, the impact of all the main CPBLS parameters controlling the sintering of dip-coated Cu-doped HA layers on glass substrates is carefully investigated. Possibility of the creation of thin consolidated Cu-doped HA ceramic patterns, using the ultra-fast CPBLS process, is finally shown.